تأثير تدفق الإستثمار الأجنبي المباشر على أداء التجارة الدولية - بن ساحة, زهرة (My University, 2022)
The study aims to analyze the relationship between foreign direct investment and international trade in Algeria during the period between 2000-2019, given the importance of foreign direct investment as an important source of external financing and economic development, the latter being one of the main issues that occupy the minds of decisionmakers. political and economic in the country. Where Algeria tried to advance its economy and create the appropriate climate to attract foreign capital and liberalize its international trade with the aim of transforming Algeria into a suitable investment environment. It has also witnessed in recent years a rise in its exports compared to imports, a surplus in the trade balance and an increase in the volume of foreign direct investment. The latter is considered one of the factors causing international trade. On the one hand, foreign investment stimulates exports, and on the other hand, foreign direct investment affects imports
دراسة حالة الجزائر
Keywords: Foreign direct investment - international trade –exportsimports- a case study of Algeria.